Compiling Vector Pascal to the XeonPhi. (18th May 2015) - Chimeh, Mozhgan; Cockshott, Paul; Oehler, Susanne B.; Tousimojarad, Ashkan; Xu, Tian
Summary: Intel's XeonPhi is a highly parallel x86 architecture chip made by Intel. It has a number of novel features which make it a particularly challenging target for the compiler writer. This paper describes the techniques used to port the Glasgow Vector Pascal Compiler to this architecture and assess its performance by comparisons of the XeonPhi with 3 other machines running the same algorithms. Copyright © 2015 John Wiley & Sons, Ltd.